(untitled) (The Review of Diabetic Studies, 2024)
The evaluation of pharmaceutical care services in Middle Eastern countries is crucial for understanding and enhancing the role of pharmacists in improving patient outcomes within diverse healthcare systems. Pharmaceutical care is a patientcentered approach that focuses on the safe and effective use of medications through comprehensive management, including the assessment of medication needs, the development of individualized treatment plans, and ongoing monitoring. As healthcare systems in the Middle East undergo significant transformation due to rapid economic growth and increasing healthcare demands, the integration of pharmaceutical care services has become increasingly prominent. This review article aims to assess the current state of pharmaceutical care services across various Middle Eastern countries, highlighting both achievements and challenges. The evaluation encompasses factors such as healthcare infrastructure, regulatory frameworks, and cultural attitudes towards medication management, which significantly influence the implementation and effectiveness of these services. Despite notable advancements in some countries, such as the United Arab Emirates and Saudi Arabia, disparities remain in the accessibility and quality of pharmaceutical care services across the region. Furthermore, the article examines the impact of pharmaceutical care on patient outcomes, including medication adherence, chronic disease management, and overall patient satisfaction. It identifies barriers to effective pharmaceutical care, such as insufficient training for pharmacists, regulatory limitations, and varying public awareness of pharmacists’ roles. Additionally, the review explores opportunities for enhancing pharmaceutical care services, including the need for workforce development, policy advocacy, and the integration of technology in healthcare delivery. Ultimately, this evaluation seeks to provide a comprehensive understanding of the landscape of pharmaceutical care services in the Middle East, offering insights into best practices and strategies for improvement. By fostering collaboration among healthcare professionals, policymakers, and educational institutions, the region can advance its pharmaceutical care services, leading to improved health outcomes and a more effective healthcare system overall.